2021
DOI: 10.1155/2021/6619768
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Healthcare Workers Knowledge and Attitude on Infection Prevention and Control: A Case of Tamale Teaching Hospital, Ghana

Abstract: Background. Most morbidities and mortalities related to clinical, diagnostic, and therapeutic procedures are related to infection and the solution to this is good infection prevention and control (IPC) compliance which is influenced by the right knowledge and positive attitude. Aim. This study aimed to assess infection prevention and control (IPC) knowledge and attitude among healthcare workers at the surgical department of Tamale Teaching Hospital (TTH). Methods. This study was conducted using a descriptive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…This conclusion is similar to that of study findings[ 27 ] who found that the amount of practice was >58%. However, it is lower than the 74% discovered by research evidence,[ 10 ] but it is greater than many other studies, which revealed that this level of practice accounted for 52%[ 28 ] and 58%,[ 29 ] respectively. This gap in results could be attributable to individuals' differing views toward using infection control measures.…”
Section: Discussionmentioning
confidence: 61%
“…This conclusion is similar to that of study findings[ 27 ] who found that the amount of practice was >58%. However, it is lower than the 74% discovered by research evidence,[ 10 ] but it is greater than many other studies, which revealed that this level of practice accounted for 52%[ 28 ] and 58%,[ 29 ] respectively. This gap in results could be attributable to individuals' differing views toward using infection control measures.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, Alhassan et al from Ghana, in 2021, reported that 97.4% ( p ≤ 0.001) of respondents agreed to wash their hands following the removal of gloves. About 95.5% of respondents believed that following prevention guidelines would reduce HAI rates, and 86% agreed that following the SOPs would decrease the risk of contamination 36 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that unmarried nurses had better knowledge than married nurses, possibly because unmarried nurses might spend less time with their families and so had more time for attending the training course on ADs. In a survey study of surgical healthcare workers' knowledge of infection prevention and control, marital status ( p = .030) was one factor associated with the knowledge level (Alhassan et al., 2021). A correlation between marital status and knowledge was established in a study in which divorced or widowed nurses (83.3%) had more adequate knowledge of COVID‐19 (Tamang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%